The evaluation of knowledge and perception on home kitchen cleanliness for the preparation of commercial foods - Abu Bakar, Ibrahim; Zakaria, Zahidatul Farihah; Mohd Shahizi, Nor Syamimi (Asian Scholars Network, 2025)
Abstract: Home kitchen are used by food entrepreneurs to prepare commercial foods since COVID-19 pandemic until today as it is easier and cheaper. However, the level of cleanliness is still doubtful. The level of knowledge regarding home kitchen cleanliness among Malaysian people also still uncertain. Thus, this cross-sectional study was designed to assess the knowledge of consumers regarding home kitchen cleanliness as well as perception on home-based food business. A total of 439 respondents from all state in Malaysia was conveniently recruited to take part in this study. They were required to answer a set of questionnaires which consisted of three sections: sociodemographic, level of knowledge regarding home kitchen cleanliness and perception regarding home-based food business. For the level of knowledge regarding home kitchen cleanliness, scoring system was used and each has a score ranging from 1 to 6 which total score is 178. The maximum score was divided by total score and changed to a percentage value. The score which is less than 50% indicated poor knowledge, 51-70% shows average level of knowledge, 71% until 85% indicates good knowledge and above 86% shows excellent level of knowledge. For the section of perception towards home-based food business, the questions consisted of three choices of answer which are agree, partially agree and disagree. More than half of participants had an excellent knowledge regarding home kitchen cleanliness. There was a significant difference (p-value < 0.05) between the level of knowledge with marital status, size of the kitchen, and practicing home-based food business while no significance difference (p-value > 0.05) was found in gender, race, and educational level. Furthermore, more than 70% of respondents agree that preparation of commercial food can be done at home, which indicates people start to accept home-based food business nowadays. This research achieved the objectives as well as the government expectation, especially the Ministry of Health, for a future plan of a suitable intervention by providing systematic campaigns toward home kitchen cleanliness.